Factores de riesgo asociados al deterioro cognitivo leve en adultos mayores de los Centros del Patronato de Amparo Social del cantón Loja - Figueroa González, Doris Vanessa (2019)
The sociodemographic risk factors and emotional states that prevail in individuals increase the probability of receiving a diagnosis of mild cognitive impairment (MCI), so that the existing research has as an objective to stablish the risk factors that are associate with mild cognitive impairment in senior citizens of Patronato de Amparo Social of the Loja canton. For this, it was collected information about 20 senior citizens of both genders, with ages between 65 and 85 years old. The investigation was descriptive, transversal, with quantitative approach; The data collection instrument system was made up of a sociodemographic questionnaire, the NEUROPSI reagent (Brief Neuropsychological Evaluation in Spanish), Anxiety and Beck Depression Inventory. After analyzing the data, we were able to determinate that the prevalence of MCI among senior citizens of the Patronato de Amparo Social centers consists of about 62, 5%; with respect to the sociodemographic profile, 75% of the participants were male, 50% in ages between 80 and 85 years old, with respect to levels of instruction, 40% had incomplete schooling, and 75% of the sample have worked in a manual job during their lives; after the used of the of the corresponding statistical programs it was found a significant relation between incomplete schooling and MCI. With respect to emotional states, depression was associated with the appearance of MCI, not being so with anxiety. Keywords: aging, affective states, risk factors, education.